3D‐Printed Acoustofluidic Devices for Raman Spectroscopy of Cells. Issue 10 (19th August 2021) - Santos, Harrisson D. A.; Silva, Amanda E.; Silva, Giclênio C.; Lima, Everton B.; Marques, Alisson S.; Alexandre-Moreira, Magna S.; Queiroz, Aline C.; Jacinto, Carlos; Henrique Lopes, J.; Rocha, Uéslen; Silva, Glauber T.
Abstract : Acoustofluidics technology can be used to trap live cells (and also micro/nanoparticles) in microenvironments suitable for cell assays. Herein, a cheap and easy‐to‐fabricate device is proposed that works with Raman spectroscopy for biosensing applications. The device comprises a 3D‐printed microchamber working as a half‐wavelength acoustic resonator. By tuning the resonance frequency with a low voltage (≈4 V), cells or particles are aggregated and levitated in seconds by the action of the acoustic radiation force. Based on finite element simulations, the radiation force field produced inside the device is described. In the cellular enrichment (aggregation) process, a metastable honeycomb lattice is formed mostly due to the cell‐to‐cell attraction caused by the secondary acoustic radiation force. Orderly and metastable levitating aggregates provide an excellent arrangement for Raman spectroscopy to investigate cells individually. Polystyrene particles are used for the device characterization and Raman acquisition process. Biosensing applications are showcased with live murine macrophages J774.A1, which are used in infection assay of leishmaniasis disease. The unique features of the device, e.g., simple fabrication process with cheap materials, simple operation, fast time response, and formation of metastable cellular aggregates; hold a noteworthy potential for applications in life sciences and biotechnology involving cell assays. Abstract : Acoustofluidics technology is used to assist Raman biospectroscopy in avoiding substrate signal interferences while keeping cells alive. An integrated device is fabricated by additive manufacturing. The functioning principles and numerical system design are presented in detail. The obtained cellular spectrum shows enhanced quality as compared with conventional Raman methods.